ANALISIS PERAN KEPALA MADRASAH SEBAGAI SUPERVISOR DAN PENILAIAN PRESTASI KERJA GURU DI MAN 1 MARTAPURA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN DI ERA INDUSTRI 4.0 - Suraijiah, Suraijiah (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
The focus studied includes; The role of the Madrasah Head as a supervisor, the role of the Madrasah head in assessing teacher work performance and Factors Influencing the Madrasah Head in Teacher Performance Evaluation. The subject of the study was the head of the madrasa as the Top Leader at MAN 1 Martapura. The analysis process was carried out by examining all data generated from interviews, observation results and documentation results related to the role of the head of MAN Martapura 1 as Supervisor and assessing teacher performance, as well as the factors that influence it. This study shows that the role of the madrasa head at MAN 1 Martapura is quite well implemented. The role of the madrasa head as coordinator, consultant, group leader and evaluator is also influenced by several factors, namely educational background, teaching experience, funds and infrastructure. Another finding from the results of this study shows that the success of a madrasa is actually the result of cooperation and shared responsibility of all components in the school, so synergy needs to be built in the management of a madrasa. Assessment of teacher achievement is very important as a benchmark for achieving teacher teaching achievement